The Analysis of a Wideband Strip-Helical Antenna with 1.1 Turns - Xihui Tang; Botao Feng; Yunliang Long (International Journal of Antennas and Propagation)
A wideband strip-helical antenna with 1.1 turns is analyzed numerically and experimentally. By replacing the traditional wire helix with wide metallic strip, the forward traveling current on the strip helix with about one turn smoothly decays to the minimum value at the open end of the helix. Therefore, the strip helix can excite a wideband circular polarization (CP) wave with 50-ohm impedance matching. The proposed antenna is printed on a hollow-cylinder with a substrate relative permittivity of εr=2.2 and a thickness of h=0.5 mm. A 50 Ω coaxial cable is directly connected to excite the strip-helical antenna without any additional impedance matching section. The ground plane is placed below the antenna in order to provide a directional radiation pattern. To demonstrate this method, a prototype of 1.1-turn strip-helical antenna is tested. The test shows that the proposed antenna can reach an overlapped bandwidth of 46% with height of 0.52λ0, where λ0 is the wavelength in free space at the center operation frequency.